Vitamin A: too good to be bad? - Chen, Guoxun; Weiskirchen, Sabine; Weiskirchen, Ralf (Frontiers in Pharmacology, 2023)
Vitamin A is a micronutrient important for vision, cell growth, reproduction and immunity. Both deficiency and excess consuming of vitamin A cause severe health consequences. Although discovered as the first lipophilic vitamin already more than a century ago and the definition of precise biological roles of vitamin A in the setting of health and disease, there are still many unresolved issues related to that vitamin. Prototypically, the liver that plays a key role in the storage, metabolism and homeostasis of vitamin A critically responds to the vitamin A status. Acute and chronic excess vitamin A is associated with liver damage and fibrosis, while also hypovitaminosis A is associated with alterations in liver morphology and function. The hepatic stellate cells that are the main tissue site of vitamin A storage to support vision and development have in addition multiple physiological roles from balancing retinol toxicity to mediating inflammatory responses in the liver. Strikingly, different animal disease models also respond to vitamin A statuses differently or even opposing. In this review, we discuss some of these controversial issues in understanding vitamin A biology. More studies of the interactions of vitamin A with animal genomes and epigenetic settings are anticipated in the future.